TOURISM KNOWLEDGE MANAGEMENT IN BOGOR SMART CITY - Pipin Noviati Sadikin; Erie Hermawan Atmawidjaya (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2023)
The Bogor City as tourism destination applies the Smart City concept to its city planning, with the aim that the Bogor City can overcome various urban problems in order to realize sustainable development goals in accordance with the Sustainable Development Goals. Processing and managing information and knowledge using the Knowledge Management concept in Smart City can help organizations to be more prepared and organized to face a level of competition with their competitors and create new innovations for the products or services they have. This research uses a qualitative descriptive method, using a Google Form questionnaire, literature study and observation. This research aims to examine Knowledge Management or the management of tourism information and knowledge in the Bogor Smart City, as well as identifying what the challenges are and the community's experiences in participating in Knowledge Management of the Bogor Smart City.